Educação estética e formação inicial de professores da educação básica: um estudo hermenêutico do projeto político-pedagógico do curso de pedagogia, na modalidade de educação a distância - Santos, Antonio Carlos Banzato Afonso (2011)
The purpose of this work is to present Aesthetic Education in initial teacher training. The issue investigated is the meaning of Aesthetics in the Political Pedagogical Project (PPP) – Distance Education modality — of University of Santo Amaro — UNISA’s Pedagogical School, located in the south area of the city of São Paulo. The aim of this study is to understand how important Aesthetics is in the process of developing autonomy and emancipation of individuals in the School of Education – Distance Education modality. The hypothesis is that the development of autonomy and emancipation that enhances the agency of the individuals in society occurs by aesthetic means. Adorno’s theoretical framework focusing on understanding the aesthetic parameters in the cultural industry and mass culture is used, as well as Freire’s theoretical framework, regarding Banking Education, in order to overcome it through aesthetic curiosity and epistemological curiosity as a way of awareness provided by aesthetic education. Schiller’s approach is used regarding the sensitive dimension of art in the process of teacher development training. The procedure to collect data was document analyses which were interpreted according to Gadamer’s perspective of Hermeneutics. The outcome of this study is a reflection on the introduction of Aesthetics in teacher education as a possibility to release the Banking teacher of the Pedagogy course, considering Distance Education, as well as art as a way to pursuit awareness in the individual relationship with oneself and with the world. The opposition to the Banking Education provides the development of awareness of the individual concerning the aesthetic manipulation inherent to the cultural industry. This humanization, which enhances the role of experience of the individual student, enables the understanding of the existential situation in which the individual belongs to